Ensiffer sp. CNN3 -an indigenous bacterial strain in Vietnam has properties of plant growth promotion and organophosphorus degradation - Chi, Hoang Kim; Cuong, Le Huu; Ha, Tran Thi Hong; Ha, Nguyen Thu; Thanh, Luong Huu; Nga, Vu Thuy; Huong, Le Mai; Hang, Tran Thi Nhu (Vietnam Journal of Science and Technology, 2021)
An indigenous effective bacterial strain has been isolated from soil samples of contaminated tea farming site in Northern Vietnam with chlorpyrifos degradability and plant growth promoting characteristics. The bacterial isolate was determined to belong to genus Ensifer (syn. Sinorhizobium), and its degrading property for OPP substrate chlorpyrifos in culture as well as in test soil were studied. The results open a prospect of applying the dual-effective bacterial strain in agriculture practices either to reduce the use of chemical fertilizer or to remediate OPP contaminated planting soils.